1999
DOI: 10.1002/(sici)1521-3773(19990712)38:13/14<1934::aid-anie1934>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Coordination Polymer with an Expanded NbO Structure

Abstract: The connection of square‐planar [Ni(CN)4]2− ions with Ph3Sn+ ions results in 1, a noninterpenetrated three‐dimensional coordination polymer with an expanded NbO structure. The (Ph3Sn)2Ni(CN)4 framework (shown schematically without phenyl groups and solvent molecules) displays a large central cavity that is occupied by Ph3SnOH, acetonitrile, and water molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 18 publications
(45 reference statements)
3
36
0
Order By: Relevance
“…It was suggested that, among numerous topological nets, the most important and plausible targets for designed synthesis are those with “simple, high‐symmetry” structures 4. However, only a very limited number of types of simple three‐dimensional (3D) 3‐connected2 and 4‐connected nets based solely on square‐planar nodes, such as the cubic NbO (6 4 8 2 ),3a,b tetragonal CdSO 4 (6 5 8),3c “dense net” (7 5 9),3d and 4.4.8 4 .8 4 .8 8 .8 8 3e nets have been reported so far, in contrast to the widely established 2D 3‐connected honeycomb or brickwall (6 3 ) and 4‐connected square grids (4 4 ) 1. Meanwhile, some 3‐connected nets can be described as augmented 4‐connected nets by substituting four adjacent 3‐connected nodes for 4‐connected nodes,4, 5 for example, 4.8 2 for 4 4 , 4.12 2 for NbO (6 4 8 2 ), and 4.14 2 for diamond (6 6 ) 2c…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that, among numerous topological nets, the most important and plausible targets for designed synthesis are those with “simple, high‐symmetry” structures 4. However, only a very limited number of types of simple three‐dimensional (3D) 3‐connected2 and 4‐connected nets based solely on square‐planar nodes, such as the cubic NbO (6 4 8 2 ),3a,b tetragonal CdSO 4 (6 5 8),3c “dense net” (7 5 9),3d and 4.4.8 4 .8 4 .8 8 .8 8 3e nets have been reported so far, in contrast to the widely established 2D 3‐connected honeycomb or brickwall (6 3 ) and 4‐connected square grids (4 4 ) 1. Meanwhile, some 3‐connected nets can be described as augmented 4‐connected nets by substituting four adjacent 3‐connected nodes for 4‐connected nodes,4, 5 for example, 4.8 2 for 4 4 , 4.12 2 for NbO (6 4 8 2 ), and 4.14 2 for diamond (6 6 ) 2c…”
Section: Methodsmentioning
confidence: 99%
“…The 4.12 2 net can also be simplified to an NbO net (Figure 2 c) if each {Cu 2 (ptz) 2 } subunit (Figure 2 a) is considered as 4‐connected node,4 an example distinct from the rarely observed, true 4‐connected NbO nets 3a. b Similar to other NbO nets, the network of 2 also contains channels, which are mainly occupied by the disordered propyl groups.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D crystal structure of 2 is shown in Figure 2 c. The structure contains two interpenetrated frameworks based on the 6 4 8 2 topology (Figure 2 d). [21][22][23] Although interpenetration occurs in this structure, it features 1D channels along the c direction. The diameter of each hexagonal channel is about 1.1 nm.…”
mentioning
confidence: 91%
“…75 The chiral three-dimensional coordination polymer based on Zn 2 and the achiral ligand [L 68 ] À contains two intersecting 6-fold helices, and has modest second-order non-linear optical activity which is allowed by the non-centrosymmetric structure. 85 Catenates, rotaxanes and knots [Li 3 (L 72 ) 2 ] 3 is a trinuclear double helicate; linking the open ends by a ring-closing metathesis reaction results in a doubly interlocked [2]catenane (Fig. 77 Other networks with threefold symmetry have been prepared from copper(I) halides and 1,3,5-triazine.…”
Section: Other Coordination Oligomers and Polymersmentioning
confidence: 99%